Comparative Investigation on the Anatomical,Chemical characteristics of E.camaldulensis From region jiroft - Saeideh Sharifi (Regional Information Center for Science and Technology (RICeST), 2008)
Okaliptus is a fast –growing and light – liking tree that its trunk is smooth and is shelled spontaneously. n a short time its diameter and height increase.for its fast growing. So that turing it into things is difficult Fiber s traction is high and deksity is 0.55 to 0.58 a square centimeter. The samples were prepared from the branches and trunk of Ocalyptus Kameldolensis with the average old  of three years, from Jiroft region in Kerman province. After ordaining the age and having samples from the same age , some discs were prepared for cutting to measure fibers.Making ready and suspension of fibers were done in Fraklin method .Measuring  amaout of lignin was done to standard  no: T222- om – 88 and  TAPPI guide directions . Measuring cellulose was done according to  Nitric Acid  method and due to standard  No : T264 – om – 88 , and TAPPI guide directions.   Due to results the length of trunk fibers was 811.36 and branches was 845.68 micro meters.Diameter of trunk fibers is 19.3 but branches 15.64, these amounts don,t have a meaningful differnce the level of 5&1 percent . Diameter of the carity of rrunk fibers was 10.71, but branches 3.44 at the level of 5&1 percent , they don,t have a meaningful difference. The amount of extracted articles of trunk is 4/5 but branches 2.3 percent ,and amount of lignin in trunk was 35.66 but in the branch 24.66, and amount of cellulose in trunk was 55.66 and the branch 46.81 percent which at the level of 5&1 percent have a meaningful difference . The amount of Ashes  from trunk was 0.73 but from the branch 0.88 that at the level of 5&1 percent , don,t have a meaningful defference.